2020
DOI: 10.1109/access.2020.3020282
|View full text |Cite
|
Sign up to set email alerts
|

16-Port Non-Planar MIMO Antenna System With Near-Zero-Index (NZI) Metamaterial Decoupling Structure for 5G Applications

Abstract: In this article, a low-cost 16-port non-planar Multiple-Input-Multiple Output (MIMO) antenna system is proposed for future 5G applications. The non-planar MIMO antenna system is established around a 3D-octagonal-shape polystyrene block. The MIMO elements are arranged on the eight-sides of octagonalshape block, whereas bottom and top faces of polystyrene block are left void. The single antenna element comprises of slotted microstrip patch with a stepped chamfered feed line and defected ground plane. Each MIMO e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 35 publications
0
25
1
Order By: Relevance
“…The performance of the mm-Wave two-port MIMO antenna systems evaluated by TARC, ECC, and CCL. These performance parameters are extracted by using the Equations (1) for ECC, (2 and 3 ) for CCL and TARC [30]. In mm-wave applications, the values of TARC, CCL, and ECC should be lower than 0 dB, 0.5 bits/s/Hz, and 0.5, respectively, for an efficient system of MIMO antenna [30][31][32].…”
Section: Resultsmentioning
confidence: 99%
“…The performance of the mm-Wave two-port MIMO antenna systems evaluated by TARC, ECC, and CCL. These performance parameters are extracted by using the Equations (1) for ECC, (2 and 3 ) for CCL and TARC [30]. In mm-wave applications, the values of TARC, CCL, and ECC should be lower than 0 dB, 0.5 bits/s/Hz, and 0.5, respectively, for an efficient system of MIMO antenna [30][31][32].…”
Section: Resultsmentioning
confidence: 99%
“…7 for the unit cell of the MTM along with 1 × 2, 2 × 2, and 2 × 2 arrays conditions. Prior to the analysis of the MTM effective parameters, stopband behaviour was first investigated to enable the proposed MTM to be operated in different microwave applications [16,38]. From the Sparameters, it could be observed that the stopbands are created when the S 21 results are below −10 dB, and the S 11 results are near to zero.…”
Section: Modelling and Simulationmentioning
confidence: 99%
“…Negative permeability, permittivity and refractive index are some exclusive properties of the metamaterial that can be used for various applications in communication systems of microwave frequencies. Antenna performance improvement 1 3 , radiation reduction 4 , 5 , design of absorber 6 , 7 , sensors 8 , 9 , high-frequency communications 10 , 11 , solar energy harvesting 12 , 13 , electromagnetic shielding 14 , metamaterial lenses 15 , etc. are some prominent applications of the metamaterial.…”
Section: Introductionmentioning
confidence: 99%